An Optimal Adaptive Traffic Signal Control Algorithm for Intersections Group - Wei Cheng; Xiaolan Liu; Wenfeng Zhang (2006 6th World Congress on Intelligent Control and Automation, 2006)
This paper puts forward an adaptive traffic signal control algorithm for intersections group, which is believed to make real-time signal control and yield a lot of traffic light switching schemes according to the changing of traffic conditions. The principle of the algorithm is to minimize some objective function derived from a real-time queue length mode that has been initiated in the paper, of which the character is an optimization over a fixed number of switch-overs but not a fixed number of time steps. The performance of the algorithm is proven to improve the intersection capacity by reducing the waiting time of vehicles